Cotinine as a marker for risk prediction in the Ludwigshafen Risk and Cardiovascular Health Study - Delgado Gonzales de Kleber, Graciela; Krämer, Bernhard; März, Winfried; Kleber, Marcus E. (Respiratory physiology & neurobiology, 2015)
Background: Cotinine is one of the major metabolites of nicotine. The aim our study was to investigate cotinine as a marker for individual risk prediction in the Ludwigshafen Risk and Cardiovascular Health study. Methods: 840 samples had detectable cotinine measured using a radioimmunoassay (RIA nicotine metabolite, DPC Biermann GmbH). The distribution of risk factors across quartiles of cotinine or pack-years was analyzed by ANOVA and the association of cotinine and pack-years with mortality by Cox regression. Results: Cotinine and pack-years both showed significant association with mortality in adjusted models with HRs (95% CI) of 1.30 (1.17-1.44) and 1.26 (1.13-1.42) comparing the third to the first tertile for cotinine and pack-years, respectively. Either cotinine or pack-years or self-reported smoking increased the area-under-the-curve significantly as compared to a basic model including other risk factors. Discussion: Cotinine is a strong predictor of mortality in non-smokers as well as in smokers. As objectively measurable parameter cotinine would be preferable for risk prediction.